Human Resource Development Management to Build Public Trust in MTsN 2 Rejang Lebong - Aglesia, Ade Sonnie; Komaria, Siti; Yanto, Murni; Mustar, Saidil (JIEM (Journal of Islamic Education Management), 2025)
This study aims to analyze the strategic management of human resource (HR) development for educators in enhancing public trust in Islamic educational institutions, particularly at MTs Negeri 2 Rejang Lebong. The research employs a descriptive qualitative approach through a literature study combined with a case study. The findings indicate that the current HR development strategy at the institution faces significant challenges, especially in terms of low digital literacy among teachers, uneven pedagogical competencies, and limited character development initiatives. In the Islamic perspective, the characteristics of quality educators include professional competence, spiritual integrity, and moral exemplarity. When teachers are able to serve as inspirational figures and adapt to contemporary challenges, they not only improve the learning process but also play a crucial role in building a positive institutional image. Public trust is strongly influenced by the quality of interaction and integrity demonstrated by educators. Therefore, effective and values-based HR management is essential for strengthening the reputation and public confidence in Islamic educational institutions.